Effect of type-III Anti-Freeze Proteins (AFPs) on CO2 hydrate formation rate. (10th August 2017) - Zhou, Hongxia; Infante Ferreira, Carlos
Highlights: CO2 hydrate slurry has a high latent heat at temperatures in the range of 7–8 °C. The formation of CO2 hydrate slurry in a tube generator is extremely fast. Antifreeze Proteins (AFPs) are investigated as hydrate formation limiter. The CO2 dissolution rate significantly decreases with the addition of 10 ppm AFPs. AFPs reduce CO2 hydrate formation rate by decreasing the mass transfer coefficient. Abstract: CO2 hydrate slurry is a favourable direct coolant of fresh products due to its large latent heat and phase change temperature around 7 °C. Continuous production of this slurry is, however, difficult to realise due to the high rate of hydrate formation. The use of additives is proposed with the purpose of decreasing the formation rate so that the controllability of the process is improved. Type-III Antifreeze Proteins (AFPs) are non-poisonous additives which, at low dosage, have proven to be efficient limiters of gas hydrate formation. The effect of these additives on the CO2 hydrate formation rate is experimentally investigated in this study. The concentration of the AFPs investigated in this research is 10 ppm. Experimental results show that the supercooling degree of the solution is only slightly affected by the addition of AFPs. Results also show that the addition of AFPs slows down the dissolution rate of CO2 gas into the aqueous solution which is the first step of gas hydrate formation. A hydrate growth equation has been used, from which the experimental mass transfer coefficient of CO2 through the solution has been derived. Results show that the decrease of hydrate growth rate with the addition of AFPs can be related to a decrease of the CO2 mass transfer coefficient which gives a lower mass transport rate from bulk liquid phase to the crystal interface.